Towards Masculinity As an Ethical Project. An Outline of the Philosophical and Social Situation - Górecki, Przemysław (ETHICS IN PROGRESS, 2018)
The article is an attempt at addressing the problem of "masculinity" as a historically privileged category in the social and philosophical tradition. In the dichotomous gender system, femininity is usually valued as aesthetic quality, while masculinity stands as an ethical value. This distinction, suggesting the subordinated and disadvantaged position of "femininity" derives from ancient philosophy and biblical tradition and was strengthened not only by philosophical writings but also by symbolic, legal, economic and social practices. By sketching a review of positions and confronting the stereotypical image of "masculinity" with the complex reality of multiple forms of masculine expressions, the article brings the situation of "masculinity" in the world organized by the phallogocentric symbolic order.